2019
DOI: 10.1002/hbm.24516
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of brain network supporting episodic memory in the absence of one medial temporal lobe

Abstract: How the brain supports normal episodic memory function without medial temporal lobe (MTL) structures has not been well characterized, which could provide clues for new therapeutic targets for people with MTL dysfunction‐related memory impairment. To characterize brain network supporting effective episodic memory function in the absence of unilateral MTL, we investigated the whole‐brain cortical interactions during functional magnetic resonance imaging memory encoding paradigms of words and figures in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…MTL resection for the treatment of medically intractable temporal lobe epilepsy is commonly associated with episodic memory impairment after surgery (Pillon et al, 1999;Savage et al, 2002). In patients with a normal range of memory capacity following unilateral MTL resection, task-based functional connectivity analysis has revealed functional reorganization in the contralesional hippocampus and medial prefrontal cortex (Jeong et al, 2019). Recently, many studies have demonstrated that the MTL forms two functionally distinct memory circuits, with each circuit delineating distinct anatomical and functional connections to other related brain regions (Kahn et al, 2008;Fanselow and Dong, 2010;Poppenk and Moscovitch, 2011;Libby et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…MTL resection for the treatment of medically intractable temporal lobe epilepsy is commonly associated with episodic memory impairment after surgery (Pillon et al, 1999;Savage et al, 2002). In patients with a normal range of memory capacity following unilateral MTL resection, task-based functional connectivity analysis has revealed functional reorganization in the contralesional hippocampus and medial prefrontal cortex (Jeong et al, 2019). Recently, many studies have demonstrated that the MTL forms two functionally distinct memory circuits, with each circuit delineating distinct anatomical and functional connections to other related brain regions (Kahn et al, 2008;Fanselow and Dong, 2010;Poppenk and Moscovitch, 2011;Libby et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…gov/afni/). More details about the memory encoding paradigm and data preprocessing have been described elsewhere (Jeong et al, 2018(Jeong et al, , 2019. Since previous studies have shown that FC during the postencoding resting-state is related to the memory performance (Tambini et al, 2010;Staresina et al, 2013;Tambini and Davachi, 2013), we thought that data that showed evident FC changes of memory related areas rather than entire data of post-encoding resting-state may possibly provide the additional information of the memory consolidation network.…”
Section: Epilepsy Fmri Datamentioning
confidence: 99%
“…The same subjects from our previous study are used in this study except for one patient who showed a severe movement artifact (Jeong et al, 2019 ). Patients who underwent unilateral MTL resection (MTLR) to treat medically intractable temporal lobe epilepsy at Seoul National University Hospital at least 1 year before recruitment and were between 19 and 50 years of age are retrospectively recruited.…”
Section: Application To the Epilepsy Fmri Datamentioning
confidence: 99%
See 2 more Smart Citations